SERVICE QUALITY FACTORS AFFECTING CUSTOMER SATISFACTION PAYMENT POINT ONLINE BANK AT KUD SIDO RUKUN LUMAJANG - Erviana Izza Salsabila; Kasno Kasno; Zainul Hidayat (International Journal of Accounting and Management Research, 2021)
Payment Point Online Bank (PPOB) is a counter for receiving electricity bill payments from PLN customers who are directly online with the bank. The existence of this service system aims to make it easy for customers to pay for electricity, anywhere, anytime, and in any way. The purpose of this study was to determine the service quality factors that affect the satisfaction of Payment Point Online Bank customers at KUD Sido Rukun Lumajang, either partially or simultaneously. The research method used is multiple linear regression statistical method. The results showed that for the variables of physical evidence, reliability, responsiveness, and assurance had no effect on customer satisfaction, for the empathy variable had an influence on customer satisfaction. With a coefficient of determination (R2) obtained at 0.205 which indicates that 20.5% customer satisfaction can be explained by the independent variables, namely physical evidence, reliability, responsiveness, assurance, and empathy, while the remaining 79.5% customer satisfaction is influenced by these variables. other variables not examined in this study. The limitation of this study is that it only examines service quality factors that affect customer satisfaction, while other variables that affect satisfaction are expected to be investigated by further researchers